Ethylene glycol-rich thermosensitive poly(ß-hydroxyl amine)s. Issue 10 (2nd October 2020) - Oh, Junki; Hong, Jeonghui; Khan, Anzar
Abstract: This work illustrates a new molecular design for preparing amphiphilic ethylene glycol-rich poly(ß-hydroxyl amine) polymers. In this design, the backbone and the termini of the side-chain represents hydrophilic parts of the polymer chain. Incorporation of a short hydrophobic alkyl segment between the hydrophilic parts endows an amphiphilic character to the material. Due to this amphiphilic nature, the polymer chains show alkyl-length-dependent thermoresponsive aggregation behavior in aqueous solutions. Graphical Abstract: